Increase in short-chain ceramides correlates with an altered lipid organization and decreased barrier function in atopic eczema patients[S] - Janssens, Michelle; van Smeden, Jeroen; Gooris, Gert S.; Bras, Wim; Portale, Guiseppe; Caspers, Peter J.; Vreeken, Rob J.; Hankemeier, Thomas; Kezic, Sanja; Wolterbeek, Ron; Lavrijsen, Adriana P.; Bouwstra, Joke A. (Journal of lipid research, 2012)
A hallmark of atopic eczema (AE) is skin barrier dysfunction. Lipids in the stratum corneum (SC), primarily ceramides, fatty acids, and cholesterol, are crucial for the barrier function, but their role in relation to AE is indistinct. Filaggrin is an epithelial barrier protein with a central role in the pathogenesis of AE. Nevertheless, the precise causes of AE-associated barrier dysfunction are largely unknown. In this study, a comprehensive analysis of ceramide composition and lipid organization in nonlesional SC of AE patients and control subjects was performed by means of mass spectrometry, infrared spectroscopy, and X-ray diffraction. In addition, the skin barrier and clinical state of the disease were examined. The level of ceramides with an extreme short chain length is drastically increased in SC of AE patients, which leads to an aberrant lipid organization and a decreased skin barrier function. Changes in SC lipid properties correlate with disease severity but are independent of filaggrin mutations. We demonstrate for the first time that changes in ceramide chain length and lipid organization are directly correlated with the skin barrier defects in nonlesional skin of AE patients. We envisage that these insights will provide a new therapeutic entry in therapy and prevention of AE.